The Evaluation of Further Complications after the Extraction of the Third Molar Germ: A Pilot Study in Paediatric Dentistry - Giacomo D’Angeli (Healthcare, 2021)
Some authors suggest germectomy to prevent the impaction of mandibular third molars, which can cause anterior crowding. The aim of the study, conducted with 2 years of follow-up, was to clarify when the extraction of the germ of the third molar is optimal, together with possible post-operative complications. A new surgical approach was performed through the application of a combined suture, which can provide better wound healing. The study was performed on 25 patients with a mean age of 15.44 ± 2.06. Based on orthodontic and surgical indications, 46 germectomies were performed. Follow-ups were conducted after 1 week, 2 weeks, 4 weeks, 1 year and 2 years. All procedures were carried out by the same operator and were standardized. Data analysis was conducted using R-Software. Statistical evaluation used the chi-squared test and the Monte Carlo test. The level of significance was set as 0.05. Results showed that out of 46 germectomies, the prevalence of complications was 4.2% for two patients (8%). Both complications were observed in male patients. In the first case, the patient (at Nolla stage 7) showed delayed onset infections after four weeks; in the second case, the patient (at Nolla stage 6) showed bleeding immediately after surgery and suture. With reference to delayed onset infections, no statistically significant association was found among gender (χ2 = 0.719; p = 0.396), germ development stage (χ2 = 2.595; p = 0.658) or Winter’s classifications (χ2 = 0.046; p = 0.829); similarly, no significant associations were found among bleeding, gender (χ2 = 0.719; p = 0.396), germ development stage (χ2 = 2.595; p = 0.658) or Winter’s classification (χ2 = 0.046; p = 0.829). From our results, it is also possible to state that post-operative complications following germectomy of the mandibular third molar germ in adolescence occur in a significantly reduced percentage of patients, so this oral surgery treatment becomes a reliable surgical technique in adolescence.